FAKTOR-FAKTOR YANG MEMENGARUHI KUALITAS AUDIT (STUDI PADA AKUNTAN PUBLIK YANG BERADA DI PROPINSI DAERAH ISTIMEWA YOGYAKARTA) - Shidqi Kurnia; Atiek Sri Purwati (Jurnal Ekonomi Dan Bisnis, 2020)
This study aims to determine the effect of independence, due professional care, work experience, motivation, gender, competence, audit fees, audit tenure, workload, and implementation of ISA standards on audit quality produced by the Public Accountant Office located in Provision D.I Yogyakarta. The sampling technique used was accidental sampling. The research sample obtained amounted to 55 respondents. Data collection method is done through a questionnaire using data analysis in the form of Multiple Regression Analysis on the SPSS v 23 for windows application, as well as documentation. The results of this study indicate that auditor independence has a significant positive effect on audit quality, Due Professional Care has a positive but not significant effect on audit quality, work experience has a significant positive effect on audit quality, motivation has a positive but not significant effect on audit quality, Gender has negatif and no significant effect on audit quality, Competence has significant positive effect on audit quality, Audit fee has positive but not significant effect on audit quality, Audit tenure has negative but not significant effect on audit quality, Workload has significant negative effect on audit quality, Implementation of ISA standard has significant positive effect on audit quality . Keywords: Independence, Due professional care, Work experience, Motivation, Gender, Competence, Audit fees, Audit tenure, Workload, Implementation of ISA standards, Audit quality.